Numerical analysis using the finite Element method to shallow reinforced Concrete - Ribeiro, Cláudio Márcio; Bomjardim, Thiago; Gomes, Romero César (Revista Hipótese, 2018)
The objective of this article is to present a case study on a solution about the Slab Foundations, which could be competitive as well as realistic. This article pretends to demonstrate the slab foundation analysis and its geometry optimization, based on three kind of soils, considering the effect of Soil-Structure Interaction (SSI). Also, proposing an ideal geometry for each kind of these geotechnical works. For the analysis was utilized a software with the capability of the Finite Element Methods (FEM), which the results are, the soil tension, the foundation settlement and the material take-off.
Keywords: Raft Foundation; Numerical Analysis; Geotechnical Characters; Finite Element Methods